Constructing Sense from Uncertain and Evolving Health Information - Genuis, Shelagh (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This qualitative study explored individuals’ everyday life experiences as they interacted with and integrated uncertain health information mediated by formal and informal sources. Findings demonstrate that knowledge translation is a multifaceted, ongoing process of social construction. The study has implications for health literacy and shared decision-making. Cette étude qualitative explore les expériences individuelles quotidiennes dans une option d’interaction et d’intégration de renseignements médicaux incertains provenant de sources formelles et informelles. Les résultats démontrent que le transfert de connaissances est un processus de construction sociale continu à multiple facettes. L’étude a des répercussions sur la littératie en santé et la décision par consensus.